2018
DOI: 10.1159/000491394
|View full text |Cite
|
Sign up to set email alerts
|

Treatment-Resistant Human Extraparenchymal Neurocysticercosis: An Immune-Inflammatory Approach to Cysticidal Treatment Outcome

Abstract: Objective: The aim of this study is to analyze the immune-endocrine profile in neurocysticercosis (NC) patients resistant to cysticidal treatment. Methods: The inflammatory and regulatory responses of 8 resistant NC patients with extraparenchymal parasites and 5 healthy controls were evaluated through flow cytometry. Serum interleukin levels were measured by ELISA and catecholamines levels by high performance liquid chromatography. Results: Higher percentages of Tr1, CD4+CD25+FOXP3+CD127– and CD4+CD45RO+FOXP3<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Although the age of the control patients in our study was higher than in the infection groups, similar levels of cytokines were shown in normal individuals who were under 45 years old and those who were over 65 years old, indicating that age does not influence cytokine production (Kim et al, 2011). Similar to the present study, in which 77% of the study subjects were males, others have reported higher numbers of male subjects in their studies, despite females being more prone to inflammatory diseases (Kashyap et al, 2012;Cavellani et al, 2012;Arce-Sillas et al, 2018). In this study, increased levels of cytokines in more than half of the patients did not correlate with CSF cellularity.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Although the age of the control patients in our study was higher than in the infection groups, similar levels of cytokines were shown in normal individuals who were under 45 years old and those who were over 65 years old, indicating that age does not influence cytokine production (Kim et al, 2011). Similar to the present study, in which 77% of the study subjects were males, others have reported higher numbers of male subjects in their studies, despite females being more prone to inflammatory diseases (Kashyap et al, 2012;Cavellani et al, 2012;Arce-Sillas et al, 2018). In this study, increased levels of cytokines in more than half of the patients did not correlate with CSF cellularity.…”
Section: Discussionsupporting
confidence: 82%
“…Additionally, in adult patients with NCC, higher levels of IL-6 were detected in CSF from patients with high cerebral blood flow velocity, which is associated with disease severity (Góngora-Rivera et al, 2008;Sáenz et al, 2012). The increased levels of proinflammatory cytokines in NCC have been shown to decrease after cure or in treatmentresistant patients (Arce-Sillas et al, 2018;Harrison et al, 2021). In vitro studies have also shown upregulation of IL-8 in monocytes in response to T. solium antigens (Uddin et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation